Heavy Metal Tolerance Genes Associated With Contaminated Sediments From an E-Waste Recycling River in Southern China - Long, Shengqiao; Tong, Hui; Zhang, Xuxiang; Jia, Shuyu; Chen, Manjia; Liu, Chengshuai (Frontiers in Microbiology, 2021)
Heavy metal pollution that results from electronic waste (e-waste) recycling activities has severe ecological environmental toxicity impacts on recycling areas. The distribution of heavy metals and the impact on the bacteria in these areas have received much attention. However, the diversity and composition of the microbial communities and the characteristics of heavy metal resistance genes (HMRGs) in the river sediments after long-term e-waste contamination still remain unclear. In this study, eight river sediment samples along a river in a recycling area were studied for the heavy metal concentration and the microbial community composition. The microbial community consisted of 13 phyla including Firmicutes (ranging from 10.45% to 36.63%), Proteobacteria (11.76% to 32.59%), Actinobacteria (14.81% to 27.45%), and unclassified bacteria. The abundance of Firmicutes increased along with the level of contaminants, while Actinobacteria decreased. A canonical correspondence analysis (CCA) showed that the concentration of mercury was significantly correlated with the microbial community and species distribution, which agreed with an analysis of the potential ecological risk index. Moreover, manually curated HMRGs were established, and the HMRG analysis results according to Illumina high-throughput sequencing showed that the abundance of HMRGs was positively related to the level of contamination, demonstrating a variety of resistance mechanisms to adapt, accommodate, and live under heavy metal-contaminated conditions. These findings increase the understanding of the changes in microbial communities in e-was\te recycling areas and extend our knowledge of the HMRGs involved in the recovery of the ecological environment.